مكانة الودائع المصرفية كمصدر لتمويل الاقتصاد الوطني في سورية - الصطوف محمد الحسين; عثمان أحمد (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن مقدرة النظام المصرفي السوري على تحويل المدخرات المحلية من أموال مكتنزة كودائع مصرفية بأشكالها المتعددة, إلى أموال منتجة وفعالة كالتسليفات التي تمنحها المصارف بأشكالها المختلفة, يجب أن تلبي احتياجات القطاعات الاقتصادية المتعددة, وتساعد في دعم عجلة النمو الاقتصادي والتنمية في سورية. تمثل الودائع الآجلة مصدراً أساسياً لتوظيفات المصارف, وتستطيع هذه المصارف تلبية احتياجات الاستثمارات المحلية, حيث تغطي ودائعها حجم الاستثمارات المحلية بعدة أضعاف, مما يدل على وجود سيولة مرتفعة لا تستثمر. إن توجه المصارف السورية في منح الائتمان غير متوازن بين تمويل جانبي الاستقرار الاقتصادي, إذ تقدم قروضاً استهلاكية قصيرة الأجل تلبي جانب الطلب أكثر من تقديمها للقروض الإنتاجية طويلة الأجل التي تلبي جانب العرض في التوازن الاقتصادي. The ability of the Syrian Banking System to transfer funds from the local savings bank deposits chunky forms, multiple funds to productive and effective loans granted by banks in their various forms, must meet the needs of various sectors of the economy, and support economic growth and development in Syria. Time Deposits could be a primary source for the banking recruitments, these banks can meet the needs for local investments, cause their deposits cover the local investments several times, which meaning there is a high liquidity without invest. The trend of Syrian banks in the granting of credit is not balanced between both sides of the financing of economic stability, providing short-term consumer loans to meet the demand side more than to the production of long-term loans that meet the supply side of the economic balance.